Microelectrothermoforming (μETF): one-step versatile 3D shaping of flexible microelectronics for enhanced neural interfaces - Dong Hyeon Lee; Younghoon Park; Yoon Seo; Hannah Noh; Hyunbeen Jeong; Jongmo Seo; Min-Ho Seo; Kyungsik Eom; Joonsoo Jeong (npj Flexible Electronics)
Abstract Increasing the proximity of microelectrode arrays (MEA) to targeted neural tissues can establish efficient neural interfaces for both recording and stimulation applications. This has been achieved by constructing protruding three-dimensional (3D) structures on top of conventional planar microelectrodes via additional micromachining steps. However, this approach adds fabrication complexities and limits the 3D structures to certain shapes. We propose a one-step fabrication of MEAs with versatile microscopic 3D structures via “microelectrothermoforming (μETF)” of thermoplastics, by utilizing 3D-printed molds to locally deform planar MEAs into protruding and recessing shapes. Electromechanical optimization enabled a 3D MEA with 80 μm protrusions and/or recession for 100 μm diameter. Its simple and versatile shaping capabilities are demonstrated by diverse 3D structures on a single MEA. The benefits of 3D MEA are evaluated in retinal stimulation through numerical simulations and ex vivo experiments, confirming a threshold lowered by 1.7 times and spatial resolution enhanced by 2.2 times.